The Use of Comic Strips to Improve Students' Skills In Writing Narrative Text at the Eleventh Grade of SMA Negeri 7 Bulukumba - Thamrin, Sri Wahyuni; Nurul Fadillah; Andi Anugrah M (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to determine whether the use of comic strips as a learning medium can improve the narrative writing skills of Grade XI students at SMA Negeri 7 Bulukumba. The research employed a pre-experimental design with pre-test and post-test procedures, involving a population of 107 Grade XI students. The sample was selected using a purposive sampling technique, specifically from class XI.2 in the 2024/2025 academic year, consisting of 25 students. Data were collected through multiple-choice tests administered as both the pre-test and post-test. The analysis revealed that the average pre-test score was 56.04, while the average post-test score increased to 78.24. Furthermore, the t-test value (4.64) exceeded the critical t-table value (1.711), indicating that the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. Based on these findings, it can be concluded that using comic strips as a teaching medium effectively enhances students' narrative writing skills at SMA Negeri 7 Bulukumba. Keywords: Comic Strips, Narrative Writing Skills,